Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.4103/1319-2442.164600
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and referral patterns of patients with chronic kidney disease in the Emirate of Abu Dhabi

Abstract: According to estimates, the dialysis prevalence in Abu Dhabi is around 370 per million population. The annual growth is 12-15% and the dialysis population is likely to double in the next five years. Most patients present to dialysis as an emergency and only 2.7% have an arteriovenous fistula at the first dialysis. The prevalence of chronic kidney disease (CKD) in the Emirate is undefined. A study of the epidemiology of CKD and referral patterns was undertaken. SEHA, the Abu Dhabi Health Service delivery compan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Data on CKD in the Middle East countries is scare but the estimated incidence of end stage renal disease (ESRD) is 100 to 140 cases per million population [2]. Epidemiological data from Abu Dhabi, United Arab Emirates (UAE) revealed that around 370 patients per million population have ESRD and are on maintenance hemodialysis [3] whereas the annual incidence of ESRD in Dubai, UAE is estimated to be 152 patients per million population [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on CKD in the Middle East countries is scare but the estimated incidence of end stage renal disease (ESRD) is 100 to 140 cases per million population [2]. Epidemiological data from Abu Dhabi, United Arab Emirates (UAE) revealed that around 370 patients per million population have ESRD and are on maintenance hemodialysis [3] whereas the annual incidence of ESRD in Dubai, UAE is estimated to be 152 patients per million population [4].…”
Section: Introductionmentioning
confidence: 99%
“…Assessing and evaluating pDDIs and ADRs among CKD patients in UAE is important as the CKD burden in the local population is high [3] and very few studies have addressed these issues in the region. On the background of these observations, the present study was conducted to evaluate pDDIs and ADRs among CKD patients.…”
Section: Introductionmentioning
confidence: 99%
“…The perceived suboptimal CKD care in this study is in agreement with recent laboratory evidence of a high frequency of undocumented CKD in the UAE and a delay in nephrology consultations. 20 Our study findings indicate that PHC facilities in the UAE provide better quality CKD care than non-nephrology SHC clinics ( figure 3 ). The ease of access to nephrology consultation at SHC facilities could contribute to this discrepancy in the practices of CKD care.…”
Section: Discussionmentioning
confidence: 61%
“…19 Access to pharmacy services and modern diagnostic laboratory support are also available at the point of care. 20 21 Nevertheless, awareness of patients and physicians of CKD is essential for effective CKD clinical practice. 22 …”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of chronic kidney disease (CKD) has increased dramatically over the past two decades, with 13.4% of the population affected worldwide; the majority of the cases are CKD stages 3–5 [ 2 ]. In a recent study, the prevalence of these disease stages among UAE nationals is 4.6% in males and 2.8% in females [ 3 ]. These results may be underestimated [ 4 ], particularly if correlated with the high prevalence of known CKD risk factors in the UAE.…”
Section: Introductionmentioning
confidence: 99%